Keeping older people mobile through a new philosophy for a new ageing population - Charles Musselwhite (Handbook of Sustainable Transport, 2020)
Older people are more mobile, wanting to stay connected to friends, family and other communities, as well as accessing services and shops and spending time carrying out leisure activities. They are likely to give up driving to changes in physiology as they age and an age friendly transport system must provide active travel and public and community transport, underpinned by age friendly policies and strategies. Applying Bourdieu’s theory of capitals to mobility, it can be seen that infrastructure capital is most important to be covered across all age friendly transport domains, but it must be supported by social capital, cultural capital and individual capital. Transport planners must recognise the increasingly diverse needs of an ageing population. There is a greater need to involve older people more in transport planning to help shape transport policies, strategies and practice. This enables different levels of capital to be appropriately resourced and provide older people with an age friendly transport system without recourse to driving and owning a car.